The dictatorship talks? reflections on the oral testimonies through interviews given by Ernesto Geisel and Jorge Oscar de Mello Flôres (Tempo e Argumento, 2010)
In this paper, we propose to undertake a reflection on the uses of oral testimony to know about historical events, especially the Brazilian dictatorship established in 1964. To this end, this work deconstructed the interviews given by Ernesto Geisel and Jose Oscar Flores to researchers from Centro de Pesquisa e Documentação de História Contemporânea do Brasil (CPDOC), Fundação Getúlio Vargas (FGV), a procedure by which we inquire into the ways in which interviewees reconstruct the events they experienced, creating a story that is the product of multiple interactions, either theirs with the interviewers and future readers, or with different time dimensions, past, present and future, which help to shape, in many ways, the memories.
Keywords: oral testimonies; dictatorship; Brazil; Ernesto Geisel; José Oscar de Mello Flôres